Transformational Leadership and Nursing Retention: An Integrative Review - Becky Goens; Natalie Giannotti (Nursing Research and Practice)
Aim. To establish current evidence on the relationship between transformational nursing leadership and turnover intention. Background. The persistent nursing shortage in healthcare has led to heightened demands for addressing both current needs and the healthcare requirements of a growing population. Recognizing the pivotal role of nursing leadership in fostering retention, this review highlights the influence of positive leadership on nursing staff. Evaluation. An integrative review, guided by Whittemore and Knafl’s (2005) framework, was conducted using articles sourced from four online databases deducing to an inclusion of sixteen quantitative articles, one systematic review, and one integrative review published between 1992 and 2022. Key Issues. The study reveals conflicting evidence regarding the sole impact of transformational leadership on the nursing staff’s intention to remain. However, it highlights transformational leadership’s ability to enhance job satisfaction and organizational commitment contributes significantly to retention. Conclusion. Using transformational leadership can effectively bolster nursing staff retention along with promoting other favorable workplace outcomes. Implications for Nursing Management. This review underscores the importance of enhancing leadership skills within nursing management. This involves not only fostering transformational leadership but also cultivating positive work-related outcomes to optimize nursing staff retention.